Accelerating Reform within Iraq’s National Board of Pensions - Alkhoja, Ghassan (World Bank, Washington, DC, 2012)
The Iraqi National Board of Pensions (NBP) has the responsibility of overseeing the oldage and disability pensions of public and private sector workers across the country. For the last several years, the NBP has been implementing an ambitious and far-reaching program of reform and renewal. Finally, the organization was not taking the time to cultivate the management skills of middle and front-line staff.